Objectively Measured Intensity-specific Physical Activity and Hippocampal Volume Among Community-dwelling Older Adults - Masaki Machida; Tomoko Takamiya; Shiho Amagasa; Hiroshi Murayama; Takeo Fujiwara; Yuko Odagiri; Hiroyuki Kikuchi; Noritoshi Fukushima; Mitsuo Kouno; Yu Saito; Fumitoshi Yoshimine; Shigeru Inoue; et al. (Journal of Epidemiology, 2022)
Background: The hippocampus is a brain structure important for memory and cognitive function. Physical activity may help prevent hippocampal atrophy. However, few studies have measured sedentary behavior (SB) and intensity-specific physical activity using an accelerometer. This study aimed to examine the cross-sectional associations of objectively-determined SB, light-intensity physical activity (LPA), and moderate-to-vigorous physical activity (MVPA) measured by an accelerometer with hippocampal volume among community-dwelling older adults using compositional data analysis (CoDa) approach. Methods: This cross-sectional study was part of the Neuron to Environmental Impact across Generations (NEIGE) study. A randomly recruited sample of 485 Japanese older adults (47% male; aged 65–84 years) wore tri-axial accelerometers (Omron Healthcare) for 7 consecutive days in 2017. Hippocampal volume was measured with magnetic resonance imaging and the left and right hippocampal volumes were automatically segmented using FreeSurfer software. Associations of sedentary and physically active behaviors with hippocampal volume were examined with compositional linear regression analysis based on isometric log-ratio transformations of time use adjusted for potential confounding factors. Results: The relative proportion of time spent in MVPA, compared to the other two activities, was significantly positively associated with right hippocampal volume (β: 57.1, P-value = 0.027). However, no association existed between higher proportions of MVPA and left hippocampal volume, or between proportions of SB or LPA with either left or right hippocampal volumes. Conclusion: The proportion of time spent in MVPA, relative to the other two activities, was significantly positively associated with right hippocampal volume. MVPA may be beneficial for maintaining hippocampal volume.